Алгоритм функціонування програмного застосунку “Аналізатор веб-контенту” - Трач, Ольга; Федушко, Соломія (Видавництво Львівської політехніки, 2016)
The specialized software for web community content analyzing based on results of the computer-linguistic analysis of web community content is designed. This software allows implementing decision support system for professionals in web community management.
Keywords: лінгво-комунікативний індикатор; веб-учасник; веб-спільнота; соціально-демографічні маркери